Implementation of IDS Using Snort with Barnyard2 Visualization for Network Monitoring in The Informatics Engineering Computer Lab at Muhammadiyah University Surakarta - Muhammad, Baihaqi Fatah; Utomo, Ihsan Cahyo (International Journal of Computer and Information System (IJCIS), 2023)
The recent surge in cyberattacks should not be taken lightly, especially by large enterprises with sensitive data. Intrusion Detection Systems (IDS) are becoming a critical component for detecting network anomalies. One such network anomaly detection tool is SNORT, with a BASE (Basic Analysis and Security Engine) frontend for efficient data processing. Acting as a bridge between SNORT and BASE, the author uses barnyard2 as a backend to store logs obtained from SNORT into the database. The implementation methodology used in this research is an experimental approach, where the authors conduct experiments through trial and error to achieve the desired results. This IDS system was tested using two types of attacks, namely DDoS and SQL-Injection. The DDoS attack trial uses tools found in Kali Linux, namely Hping3 with 6 scenarios namely FIN, ACK, RST, UDP, SYN, and ICMP with the results detected in the snort database. SQL-Injection attack test using the DVWA vulnerable website with the result detected in the snort database when the attack is carried out. This proves that the accuracy level of the system reaches close to 100% with the rules given and the penetration testing given.